Respiratory Burst Factors in Nigerian Patients with COVID-19 (Journal of Basic and Applied Research in Biomedicine, 2022)
Respiratory burst function resulting in the release of reactive oxygen species from leucocytes is one of the key mechanisms of innate immune system to prevent the establishment of intracellular pathogens in the host cells. Previous studies on COVID-19 patients concentrated on adaptive immunity while study on respiratory burst functions is lacking. Respiratory burst mediators levels [nitric oxide (NO) and hydrogen peroxide (H2O2)] and respiratory burst enzymes activities [Catalase (CAT), Myeloperoxidase (MPO) and Superoxide dismutase (SOD)] were quantitated in the plasma Mean plasma NO level, MPO activity and H2O2 level were significantly decreased while SOD activity was significantly increased in COVID-19 patients at admission compared with control. Mean plasma NO level significantly decreased while MPO activity was significantly increased in COVID-19 patients at discharge compared with control. Plasma NO level, H2O2 level and MPO activity were significantly increased in COVID-19 patients at discharge compared with COVID-19 patients at admission. In COVID-19 patients that spent ≥10days in admission, the levels of NO and H2O2 were significantly increased compared with the levels of NO and H2O2 in COVID-19 patients that spent